2018
DOI: 10.1186/s12889-018-5508-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining diffusion to understand the how of SASA!, a violence against women and HIV prevention intervention in Uganda

Abstract: BackgroundA growing number of complex public health interventions combine mass media with community-based “change agents” and/or mobilisation efforts acting at multiple levels. While impact evaluations are important, there is a paucity of research into the more nuanced roles intervention and social network factors may play in achieving intervention outcomes, making it difficult to understand how different aspects of the intervention worked (or did not). This study applied aspects of diffusion of innovations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Research could also focus on other structural issues that our systematic review uncovered such as violence (Javalkar et al, 2019;Starmann et al, 2018), stigma, discrimination and the legal status of sex work as an occupation (Blanchard et al, 2018). These social, legal, and economic injustices not only contribute to sex workers' high risk of acquiring HIV but also substance abuse, and would be important to address (Rusakova, Rakhmetova, & Strathdee, 2015).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research could also focus on other structural issues that our systematic review uncovered such as violence (Javalkar et al, 2019;Starmann et al, 2018), stigma, discrimination and the legal status of sex work as an occupation (Blanchard et al, 2018). These social, legal, and economic injustices not only contribute to sex workers' high risk of acquiring HIV but also substance abuse, and would be important to address (Rusakova, Rakhmetova, & Strathdee, 2015).…”
Section: Interventionsmentioning
confidence: 99%
“…In addition to harm-reduction research, literature recommends structural interventions in sex work contexts where substance abuse increases vulnerability to HIV including removal of legal barriers through the decriminalisation of sex work (Blanchard et al, 2018;Javalkar et al, 2019;Shannon et al, 2018;Starmann et al, 2018). Future research should, in particular, explore: (i) individual and contextual factors associated with substance use (initiation, promotion and continued use) among young people aged 18 years and below, in key population settings; (ii) pathways to substance use among under-researched groups such as uniformed personnel, truckers and miners, paying attention to the unique contribution of their work and work environments.…”
Section: Recommendationsmentioning
confidence: 99%
“…In their evaluation of the SASA! model, Starmann et al [5] found that interpersonal communication was critical to the overall success of SASA! Rwandan CA' s initial reliance on formal structures, such as umuganda, limited opportunities for reflection and interpersonal exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Community activism to shift the patriarchal norms, attitudes and beliefs that undergird IPV is one strategy that has garnered considerable attention in recent years. Rigorous trials in sub-Saharan Africa have demonstrated that community activism, mobilisation, and organised diffusion can be effective in reducing IPV [2][3][4][5]. For example, SASA!…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%
See 1 more Smart Citation